Ostmeyer Family Farms: Economic feasibility of replacing Summer fallow with Spring canola in Northwest Kansas - Ostmeyer, Jay Donald (Kansas State University, 2024)
This thesis was completed to study the economic feasibility of replacing summer fallow with spring canola in Northwest Kansas, particularly Ostmeyer Family Farms. Ostmeyer Family Farms comprises irrigated and dryland farm grounds in Thomas and Sheridan County, Kansas. The farm has been in no-till production for the past 25 years. To help improve overall profitability and combat increased chemical-resistant weeds, Ostmeyer Family Farms needs to look for an alternative management approach. This thesis outlines one alternative to summer fallow. Research was completed regarding the ability to grow and market spring canola in northwest Kansas. This research showed that the climate was particularly suited to increasing spring canola in northwest Kansas. The spring canola market is an emerging market in northwest Kansas and is feasible to ship by truck. Analysis was completed on each of the following enterprises: i) wheat after fallow, ii) wheat after spring canola, iii) chemical fallow, iv) corn, and v) spring canola. Each enterprise budget established a rotation budget of fallow wheat corn and yellow-seeded canola-wheat corn. The fallow-wheat-corn rotational budget resulted in a net loss of $48.66 per acre, while the spring canola-wheat-corn rotation budget resulted in a net loss of $52.27.
Keywords: Canola; Feasibility; Summer fallow; Spring canola; Northwest Kansas